Comparative study of diagnostic methods for determining the incidence of malaria parasite among children attending the State Specialist Hospital Ikare-Akoko, Ondo State, Nigeria - Festus Abiose Olajubu; Esther Olubunmi Ojo (Medical Laboratory Technology Journal, 2019)
Malaria is an endemic disease in Sub-Saharan Africa, and it accounts for the death of more than 1million children annually. The objective of this study was to determine the incidence of malaria parasite among children between 2-15 years of age visiting State Specialist Hospital Ikare-Akoko, Ondo State, Nigeria, using Rapid diagnostic test kits and staining methods. The study does from July to December 2017. Two millimeters of venous blood samples were collected from each of the 300 enlisted children and stored in an anticoagulated specimen bottle. Thick and thin blood films prepared from the collected samples, stained and examined for the presence of malaria parasite use the Microscope. Three Rapid diagnostic test kits were also used. Two hundred and thirty-six (78.68%) of the 300 children investigated were found to have malaria parasite infection. Gender distribution showed that more male (45.67%) were infected than females (33.01%). Infections due to age distribution revealed that children within the ages of 2-5 years were more infected (39.3%) than children in other age range (6-10 years, 23.34% and 11-15 years, 17%). There was no statistical difference in the results obtained from the various techniques used (p